STRATEGI PENGEMBANGAN EKOWISATA DI TAMAN NASIONAL SEBANGAU KALIMANTAN TENGAH - Ign. Anung Setyadi; Hartoyo Hartoyo; Agus Maulana; E.K.S Harini Muntasib (School of Business, Bogor Agricultural University (SB-IPB), 2012)
This study examines the development strategy of ecotourism in Sebangau National Park (TNS), Central Kalimantan. The purpose of this study was to formulate development strategy of TNS ecotourism. Data processing method was done performed by descriptive analysis (quantitative and qualitative), Exponential Comparative Method determined the prospective ecotourism products and Importance-Performance Analysis (IPA) used to identify ecotourism object readiness. Priority of aspects, problems, solutions and strategic were determined by Analytic Network Process (ANP) method. The main problem encountered in the development of ecotourism in the TNS were lack of infrastructure and accessibility, as well as convincing the community by the local goverment on the importance of ecotourism. The main solutions for development of ecotourism in the TNS is the provision of infrastructure and accommodation facilities. The results showed that the main strategies is to increase cooperation with stakeholders (networking) and increased promotion/information ecotourism products.Keyword: Business Strategy, Eco-Tourism, ANP, Sebangau National Parks